Selective exposure in the digital age: a systematic review of the mechanisms, contexts, and sociopsychology implications for media ecosystems(2013-2023) - Chi, Jinglin; Kamarudin, Syafila (Arts and Science Press, 2025)
Selective exposure is a complex phenomenon, and this study takes a systematic approach to reviewing its manifestations in the changing environment of new media. Following the PRISMA guidelines, a systematic review process was carried out across various databases and found 20 scholarly articles from Google Scholar, ProQuest, CNKI and Scopus for detailed analysis. This analysis, in turn, investigates the contextual evolution, motivational underpinnings, and consequences of selective exposure on both individual and societal behavior. The findings capture important transitions from conventional online spaces to algorithmically-modulated social media settings, extending the focus from politics to a wider range of public topics including health and environmental communication. Consequently, the framework suggests the interaction of cognitive dissonance, group dynamics, and technology as motivational drivers of selective exposure, highlighting the conclusion that selective exposure is the result of influences by the individual as an agent, their group affiliations, and structures. Take selective exposure as both an independent and dependent variable for inclusion within conceptual frameworks is identified, and its role as a mediating and moderating variable is identified reflecting both theoretical suitability and empirical importance. In addition to solidifying similar narratives through action and interaction, findings also suggest modes of engagement with alternate information sources—reflecting both negative consequences for agreement but potential for constructive debate—highlighting complex impacts of selective exposure across both media consumption and a more polarized society. This study shows the relevance of selective exposure research for the understanding of media behaviors, cognitive processes, and sociopolitical dynamics for future research as well its implications as sensitive to media literacy programs and policy interventions. Further, future research would benefit from interdisciplinary approaches and adaptive methodologies to grapple with the challenges of selective exposure in polarized, technology-driven media ecosystems. This review also aim to advance theory, inform policy, and create a more egalitarian and equitable digital information ecosystem.